PENGARUH LATIHAN POWER MENGGUNAKAN METODE PLIOMETRIK TERHADAP LOMPATAN DI UKM VOLI UNTAN - Rahman S, Abdul; G Simanjuntak, Victor; Hidasari, Fitriana Puspa (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe purpose of this research is "is there any influence of power exercise using pliometric method to smash jump. The purpose of this study is to increase the jump smash.Populasi in this research is amounted to 24 people. Sampling in this research use saturated sampling technique that is sample determination technique if all member of population used as sample. The method used in this research is experimental method with pre experimental form. data collection used in the form of modified vertical jump test. Based on the calculation of t test obtained t value = 4.45> t table = 2.26 and the results of research is power training using pliometric method proved to affect high jumping smash UKM VOLLY UNTAN Keywords: Plyometric, High Smash Leap.Â